KINERJA APARATUR PEMERINTAH KECAMATAN ELLA HILIR KABUPATEN MELAWI - Sri Rahayu Sari E.42009059 (FISIP Universitas Tanjungpura Pontianak, 2021)
This thesis aims to identify and analyze about the efficiency, effectiveness, fairness and responsiveness to the performance of that happening in the apparatus of the district Ella Hilir Melawi regency. The title of this essay concerns raised by the limited manpower, facilities and infrastructure, and the lack of employe education in the sub-district office. This causes failure to achieve maximum performance This study uses a descriptive type of research with a qualitative approach. The study was conducted through the steps of research such as the research literature that includes gathering the theories used as a foundation in research and research in the field of data acquisition in the form directly. Research sites in the Melawi regency. Subjects were government officials at the district office Downstream Ella associated with achieving maximum performance. The conclusion of this study is, less efficient and effective performance caused by lack of labor, education and infrastructure as well as lack of education can affect the responsiveness in completing the work. For that the performance should be improved with the addition of the labor force, especially civil servants, the addition of office facilities, going the work performance and the maximum training for the aparatur who still have a locus loud of education. Keywords : Performance, Labor, Infrastructure, Education level